Mantle geodynamics and source domain of the East Vietnam Sea opening- induced volcanism in Vietnam and neighboring regions - Nguyen, Hoang; Shinjo, Ryuichi; Tran , Thi Huong; Le, Duc Luong; Le, Duc Anh (Vietnam Journal of Marine Science and Technology, 2021)
The spreading of the East Vietnam Sea (EVS, also known as Bien Dong, or the South China Sea), leading to the occurrence of syn-spreading (33-16 Ma) and post-spreading (< 16 to present) volcanism. Syn-spreading magma making up thick layers of tholeiitic basalt with a geochemical composition close to the refractory and depleted mid-ocean ridge basalt (MORB) is mainly distributed inside the EVS basin. The post-spreading magma is widely distributed inside the basin and extended to South and SE China, Hainan island, Southern Laos (Bolaven), Khorat Plateau (Thailand), and Vietnam, showing the typical intraplate geochemistry. Basaltic samples were collected at many places in Indochina countries, Vietnam’s coastal and continental shelf areas, to analyze for eruption age, petrographical, geochemical, and isotopic composition to understand the similarities and differences in the mantle sources between regions. The results reveal that basalts from some areas show geochemical features suggesting they were derived subsequently by spinel peridotite and garnet peridotite melting, forming high-Si, low-Mg, and low-Ti tholeiitic basalt to low-Si, high-Mg, and high-Ti alkaline basalt with the trace element enrichment increasing over time. Other basalts have geochemical and isotopic characteristics unchanged over a long period. The post-spreading basalt’s radiogenic Sr-Nd-Hf-Pb isotopic compositions show different regional basalts distribute in the various fields regardless of eruption age, suggesting that their mantle source feature is space-dependent. The post-EVS spreading basalts expose the regional heterogeneity, reflecting the mixture of at least three components, including a depleted mantle (DM) represented by the syn-EVS spreading source, similar to the DUPAL-bearing Indian MORB source; an enriched mantle type 1 (EM1), and type 2 (EM2). The DM may interact and acquire either EM1 or EM2 in the sub-continental lithospheric mantle; as a result, different eruption at different area acquires distinct isotopic signature, reflecting the heterogeneous nature of the subcontinental lithospheric mantle. The study proposes a suitable mantle dynamic model that explains the EVS spreading kinematics and induced volcanism following the India - Eurasian collision from the Eocene based on the research outcomes.